The Effects of Interest Income, Fee-Based Income And E-Banking Transactions on Earnings Changes at Bank Jatim - Salsabiela Istikmal; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
One of the measures of a company's performance is the change in profit. Banks as a type of organisation whose orientation is profit, in order to increase the amount of profit, they need to increase their income. This study aims to analyse the effect of interest income, fee income and e-banking transactions on the change of profit in Bank Jatim. The multiple linear regression analysis method is used to trace the relationship between the independent variables and the dependent variable using quarterly time series data for the period 2012-2023. The results of the analysis show that the variables of interest income and e-banking transactions do not affect earnings changes, while the variable of fee-based income shows an influence on earningsearnings changes. At the same time, the independent variables have an impact on the dependent variable, as the F-test shows that the significance value is 0.000049, which is greater than the value α = 0.05. Abstrak Salah satu tolak ukur penilaian kinerja suatu perusahaan ialah pada perubahan laba. Bank sebagai jenis organisasi yang orientasinya adalah profit, untuk menaikkan jumlah laba, mereka harus menaikkan pendapatannya. Penelitian ini bertujuan untuk menganalisis pengaruh interest income, fee-based income, dan transaksi e-banking terhadap perubahan laba pada bank jatim. Metode analisis regresi linier berganda digunakan untuk menelusuri hubungan antara variabel-variabel bebas terhadap variabel terikat dengan menggunakan data time series triwulanan periode 2012-2023. Hasil analisis menunjukkan bahwa variabel interest income dan transaksi e-banking tidak mempengaruhi perubahan laba, sedangkan variabel fee-based income menunjukkan adanya pengaruh pada perubahan laba. Variabel-variabel bebas secara bersamaan memberikan pengaruh terhadap variabel terikat karena berdasarkan uji F dinyatakan bahwa nilai signifikansi berada pada angka 0,000049 dimana lebih besar dari nilai α = 0,05.